Additive contribution of microRNA-34a/b/c to human arterial ageing and atherosclerosis - Gatsiou, Aikaterini; Georgiopoulos, Georgios; Vlachogiannis, Nikolaos I.; Pfisterer, Larissa; Fischer, Ariane; Sachse, Marco; Laina, Ageliki; Bonini, Francesca; Delialis, Dimitrios; Tual-Chalot, Simon; Zormpas, Eleftherios; Achangwa, Rawlings; et al. (Atherosclerosis, 2021)
Preclinical data suggest that the ageing-induced miR-34a regulates vascular senescence. Herein we sought to assess whether the miR-34 family members miR-34a, miR-34b and miR-34c are involved in human arterial disease. Expression levels of miR-34a/b/c were quantified by TaqMan assay in peripheral blood mononuclear cells (PBMCs) derived from a consecutive cohort of 221 subjects who underwent cardiovascular risk assessment and thorough vascular examination for aortic stiffness and extent of arterial atherosclerosis. High miR-34a was independently associated with the presence of CAD [OR (95%C.I.): 3.87 (1.56–9.56); p = 0.003] and high miR-34c with the number of diseased arterial beds [OR (95%C.I.): 1.88 (1.034–3.41); p = 0.038], while concurrent high expression of miR-34-a/c or all three miR-34a/b/c was associated with aortic stiffening (miR-34a/c: p = 0.022; miR-34a/b/c: p = 0.041) and with the extent of atherosclerosis [OR (95%C.I.) for number of coronary arteries [miR-34a/c: 3.29 (1.085–9.95); miR-34a/b/c: 6.06 (1.74–21.2)] and number of diseased arterial beds [miR-34a/c: 3.51 (1.45–8.52); miR-34a/b/c: 2.89 (1.05–7.92)] after controlling for possible confounders (p < 0.05 for all). Mechanistically, the increased levels of miR-34a or miR-34c were inversely associated with expression of SIRT1 or JAG1, NOTCH2, CTNNB1 and ATF1, respectively. The association of miR-34a/c or miR-34a/b/c with CAD was mainly mediated through SIRT1 and to a lesser extent through JAG1 as revealed by generalized structural equation modeling. Leukocyte-specific ablation of miR-34a/b/c ameliorates atherosclerotic plaque development and increases Sirt1 and Jag1 expression in an atherosclerosis mouse model confirming the human findings. The present study reveals the clinical significance of the additive role of miR-34a/b/c in vascular ageing and atherosclerotic vascular disease. [Display omitted] •Increased levels of peripheral blood mononuclear cell (PBMC) miR-34a/b/c family members are associated with adverse cardiovascular risk profile.•The concurrent increase of PBMC miR-34a/b/c is independently associated with aortic stiffness and presence and extent of human atherosclerosis.•The miR-34 target SIRT1 is implicated in the miR-34a/b/c related effect in human atherosclerotic vascular disease.•Leukocyte-specific ablation of miR-34abc−/− attenuated atherosclerosis in mice.